"People centered rural development NGDOs and decentralised government / edited by D. Rajasekhar, M. K. Bhatt and Neil Webster" - "Rajasekhar, D. (ed.)" (Bangalore, 1995)
This book deals with rural development
Keywords: Rural devvelopment